Immediate Physical Therapy following Total Joint Arthroplasty: Barriers and Impact on Short-Term Outcomes. (8th April 2019) - Warwick, Hunter; George, Andrew; Howell, Claire; Green, Cynthia; Seyler, Thorsten M.; Jiranek, William A.
Abstract : Background . Recent evidence suggests benefit to receiving physical therapy (PT) the same day as total joint arthroplasty (TJA), but relatively little is known about barriers to providing PT in this constrained time period. We address the following questions: (1) Are there demographic or perioperative variables associated with receiving delayed PT following TJA? (2) Does receiving immediate PT following TJA affect short-term outcomes such as length of stay, discharge disposition, or 30-day readmission? Methods . Primary TJA procedures at a single center were retrospectively reviewed. Immediate PT was defined as within eight hours of surgery. Demographic and perioperative variables were compared between patients who received immediate PT and those who did not. We identified an appropriately matched control group of patients who received immediate PT. Postoperative length of stay, discharge disposition, and 30-day readmissions were compared between matched groups. Results . In total, 2051 primary TJA procedures were reviewed. Of these, 226 (11.0%) received delayed PT. These patients had a higher rate of general anesthesia (25.2% versus 17.8%, p=0.006), later operative start time (13:26[ 11:31-14:38] versus 9:36[ 8:24-11:16], p<0.001), longer operative time (1.8[ 1.5-2.2] versus 1.6[ 1.4-1.8] hours, p=0.002), and higher overall caseload on the day of surgery (6[ 4-9] versus 5[ 4-8], p=0.002). A matched group of patients who received immediate PT was identified. There were no differences in postoperative length of stay or discharge disposition between matched immediate and delayed PT groups, but delayed PT (OR 4.54; 95% CI 1.61-12.84; p=0.004) was associated with a higher 30-day readmission rate. Conclusion. Barriers to receiving immediate PT following TJA included general anesthesia, later operative start time, longer operative time, and higher daily caseload. These factors present potential targets for improving the delivery of immediate postoperative PT. Early PT may help reduce 30-day readmissions, but additional research is necessary to further characterize this relationship.